MORPHOLOGICAL CHARACTERISTICS FOR CLASSIFICATION OF FAMILY PLATYCEPHALIDAE IN GIANH RIVER IN THE NORTH CENTRAL PART OF VIETNAM - Tuan, Ho Anh; Bulat, Dumitru; Usatîi, Marin (CEP USM, 2014)
Analysis and identification of 35 specimens of family Platycephalidae collected in the estuary Gianh in the north central part of Vietnam. We have classified three species: Rogadius serratus (Cuvier, 1829), Sorsogona tuberculata (Cuvier, 1829) and Platycephalus indicus (Linnaeus, 1758). Which has species: Rogadius serratus (Cuvier, 1829) & Sorsogona tuberculata (Cuvier, 1829) was first discovered in the study area and northern Vietnam.

Au fost analizate şi identificate 35 specimene din familia Platycephalidae colectate în râul Gianh în partea centrală de nord a Vietnamului. Noi am clasificat 3 specii: Rogadius serratus (Cuvier, 1829), Sorsogona tuberculata (Cuvier, 1829) şi Platycephalus indicus (Linnaeus, 1758), două dintre care Rogadius serratus(Cuvier, 1829) şi Sorsogona tuberculata(Cuvier, 1829) – iniţial au fost discoperite în zona cercetată şi în Vietnamul de Nord.
CARACTERISTICILE MORFOLOGICE ALE FAMILIEI PLATYCEPHALIDAE DIN RÂUL GIANH ÎN PARTEA CENTRALĂ DE NORD A VIETNAMULUI
Keywords: Rogadius serratus; Sorsogona tuberculata; Platycephalus indicus; Platycephalidae; classification; Vietnam; Gianh river; Quang Binh; clasificare; răul Gianh